Peran Pokdarwis Patuh Angen dalam Pelaksanaan Bau Nyale 2023 di Pantai Torok Aik Belek, Kecamatan Praya Barat Daya, Lombok Tengah - Aprian Eka Pujianataa; Eko Sugiarto (PANUNTUN (Jurnal Budaya, Pariwisata, dan Ekonomi Kreatif), 2024)
Bau Nyale is a tradition of the Sasak people who live along the coast of southern Lombok, including Torok Aik Belek Beach. However, the role of Pokdarwis Patuh Angen at Torok Aik Belek Beach in the Bau Nyale tradition is less exposed. This study aims to identify the role of Pokdarwis Patuh Angen at Torok Aik Belek Beach in the Bau Nyale 2023 tradition. The results of this study show that in the 2023 Bau Nyale tradition, from before the event began until the event ended, the role of Pokdarwis Patuh Angen institutionally was minimal. This happened because the coordination of the Montong Ajan Village Government to cooperate with other stakeholders was still limited. In addition, the tight implementation time made the committee formed by appointment and made Pokdarwis Patuh Angen not involved because so far the performance of Pokdarwis Patuh Angen has not been seen. Based on this conclusion, the author suggests organizing the management of Pokdarwis Patuh Angen to be more active in the development of tourism around Torok Aik Belek Beach. Thus, in the future, the performance of Pokdarwis Patuh Angen can be seen so it is expected to be institutionally involved in the Bau Nyale tradition in the next years.